The Effect of Omni Channel Marketing on Customer Buying Interest of Fashion Products - Sari, Windi Selvina; Ahmadiono, Ahmadiono; Anggitaningsih, Retna (Eastasouth Institute, 2025)
This study aims to analyze the micro-business financing provided by Baitul Maal wat Tamwil (BMT) Balung and its impact on increasing the business capital of its clients. Micro businesses, which are typically managed by small-scale entrepreneurs, often face difficulties in accessing formal financing. Therefore, BMT Balung, as a microfinance institution, plays an essential role in providing financing to support the sustainability and development of micro businesses. This research uses a quantitative approach with a descriptive analysis method to gather data from clients who have received financing from BMT Balung. The data were obtained through interviews and questionnaires from 50 respondents who are micro-business owners. The results of the study show that the financing provided by BMT Balung significantly increases the business capital of its clients. This financing positively influences the micro businesses' ability to expand production capacity, purchase raw materials, and improve product quality. Furthermore, it has a positive impact on income and the welfare of the entrepreneurs. However, challenges in repaying installments remain a concern for some clients. The conclusion of this study is that the financing provided by BMT Balung plays a strategic role in increasing micro-business capital and supporting business development.